KRAS gene amplification in colorectal cancer and impact on response to EGFR‐targeted therapy. Issue 5 (16th March 2013) - Valtorta, Emanuele; Misale, Sandra; Sartore‐Bianchi, Andrea; Nagtegaal, Iris D.; Paraf, François; Lauricella, Calogero; Dimartino, Valentina; Hobor, Sebastijan; Jacobs, Bart; Ercolani, Cristiana; Lamba, Simona; Scala, Elisa; et al.
<x xml:space="preserve">Abstract</x> KRAS mutations are the most common oncogenic event in colorectal cancer (CRC) progression and their occurrence is associated with lack of response to anti epidermal growth factor receptor (EGFR) targeted therapies. Using preclinical models and patients' samples we recently reported that the emergence of KRAS mutations but also KRAS amplification is associated with acquired resistance to the EGFR inhibitors cetuximab or panitumumab. We reasoned that KRAS amplification may also be responsible for primary resistance to these agents. Furthermore, while the prevalence of KRAS mutations has been well established in CRC, little is known about the frequency of KRAS amplification in large CRC series. We performed a screening of 1, 039 CRC samples to assess the prevalence of KRAS amplification in this tumor type and further evaluated the role of this genetic alteration on the sensitivity to anti EGFR therapies. We detected KRAS amplification in 7/1, 039 (0.67%) and 1/102 evaluable CRC specimens and cell lines, respectively. KRAS amplification was mutually exclusive with KRAS mutations. Tumors or cell lines harboring this genetic lesion are not responsive to anti‐EGFR inhibitors. Although KRAS amplification is an infrequent event in CRC, it might be responsible for precluding response to anti‐EGFR treatment in a small proportion of patients.